2019
DOI: 10.1371/journal.pone.0212837
|View full text |Cite
|
Sign up to set email alerts
|

A non-randomized trial to assess the safety, tolerability, and pharmacokinetics of posaconazole oral suspension in immunocompromised children with neutropenia

Abstract: BackgroundPosaconazole (POS) is a potent triazole antifungal agent approved in adults for treatment and prophylaxis of invasive fungal infections (IFIs). The objectives of this study were to evaluate the pharmacokinetics (PK), safety, and tolerability of POS oral suspension in pediatric subjects with neutropenia.MethodsThis was a prospective, multicenter, sequential dose-escalation study. Enrolled subjects were divided into 3 age groups: AG1, 7 to <18 years; AG2, 2 to <7 years; and AG3, 3 months to <2 years. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 17 publications
0
31
0
Order By: Relevance
“…While the posaconazole oral formulations are approved in patients older than 13 years (USA) or 18 years (Europe), the intravenous form is only labeled for patients older than 18 years, due to potential toxicity to brain ventricle development observed in juvenile dogs [2,30]. However, many studies have reported its off-label use in pediatric patients, which could be attributed to the promising efficacy and safety profile in adults [132][133][134]. A recent population pharmacokinetic model was developed for 171 pediatric immunocompromised patients aged between 5 month and 18 years receiving one of the oral formulations, with nearly 96% of the samples being obtained after administration of the suspension [70].…”
Section: Pediatricsmentioning
confidence: 99%
“…While the posaconazole oral formulations are approved in patients older than 13 years (USA) or 18 years (Europe), the intravenous form is only labeled for patients older than 18 years, due to potential toxicity to brain ventricle development observed in juvenile dogs [2,30]. However, many studies have reported its off-label use in pediatric patients, which could be attributed to the promising efficacy and safety profile in adults [132][133][134]. A recent population pharmacokinetic model was developed for 171 pediatric immunocompromised patients aged between 5 month and 18 years receiving one of the oral formulations, with nearly 96% of the samples being obtained after administration of the suspension [70].…”
Section: Pediatricsmentioning
confidence: 99%
“…Based on a set of carefully designed and well executed clinical trials performed during the past two decades (4)(5)(6), the compound has evolved into an important option for prophylaxis and treatment of invasive opportunistic fungal diseases (IFDs) in severely immunocompromised patients. Whereas the usefulness of the initially approved oral suspension was limited by high intra-and interindividual bioavailability (7,8), the subsequently developed delayed release tablet formulation and the parenteral cyclodextrin formulation allow for more controlled administration of the compound (9)(10)(11)(12). Leading international guidelines currently recommend posaconazole for primary antifungal prophylaxis in patients with acute myeloid leukemia/myelodysplastic syndrome and prolonged neutropenia and in patients with acute graft vs. host disease following allogeneic hematopoietic stem cell transplantation, as well as second line therapy for treatment of invasive aspergillosis (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…The compound is highly protein bound with serum albumin being the predominant binding protein. Previous studies with the oral suspension have shown that posaconazole exhibits linear elimination with a high apparent volume of distribution, a slow rate of absorption (8), and varying bioavailability. Nevertheless, no distribution into deeper compartments was detectable and a one compartment pharmacokinetic model was used in previous pharmacokinetic analyses (5).…”
Section: Introductionmentioning
confidence: 99%
“…Invasive fungal infections (IFIs) represent a major cause of morbidity and mortality in high‐risk paediatric haematology‐oncology patients 1‐3 …”
Section: Introductionmentioning
confidence: 99%
“…The target posaconazole plasma concentrations (PPC) used for adult patients (≥0.7 μg/mL for prophylaxis and ≥1 μg/mL for treatment) are used also for children, although even subtherapeutic levels have showed a prophylactic effect 6‐8 . The therapeutic drug monitoring (TDM) of posaconazole is recommended, especially in paediatric patients 3,7,9,10,11 . To date, there are few studies that describe pharmacokinetics, safety and efficacy of posaconazole DRT formulation in paediatric population.…”
Section: Introductionmentioning
confidence: 99%